Regulatory Networks, Management Approaches, and Emerging Treatments of Nonalcoholic Fatty Liver Disease. (8th November 2022) - Yang, Bing; Yang, Xi; Tan, Xumei; Lu, Liqing; Fan, Wei; Barbier-Torres, Lucía; Steggerda, Justin; Liu, Ting; Yang, Heping
Abstract : The pathogenesis of NAFLD is complex and diverse, involving multiple signaling pathways and cytokines from various organs. Hepatokines, stellakines, adipokines, and myokines secreted by hepatocytes, hepatic stellate cells, adipose tissue, and myocytes play an important role in the occurrence and development of nonalcoholic fatty liver disease (NAFLD). The nuclear factor kappa-light-chain-enhancer of activated B cells (NF- κ B) contributes to the progression of NAFLD by mediating liver inflammation, immune response, hepatocyte death, and later compensatory proliferation. In this review, we first discuss the crosstalk and interaction between hepatokines, stellakines, adipokines, and myokines and NF- κ B in NAFLD. The characterization of the crosstalk of NF- κ B with these factors will provide a better understanding of the molecular mechanisms involved in the progression of NAFLD. In addition, we examine new expert management opinions for NAFLD and explore the therapeutic potential of silymarin in NAFLD/NASH.